Educational leadership research, Twitter and the curation of followership - Scott Eacott (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
For an applied field, the role of research expertise is of considerable importance. With an increasing number of school leaders turning to social media for their professional learning-as part of a broader digital turn in knowledge generation, distribution, and consumption-the argument of this paper is that the notion of research expertise in educational leadership is shifting. Traditional modes of acquiring and sustaining research capital (e.g., publications, citations, research income) have been replaced by social presence, profile building, and the curation of followership. Building on work claiming there is a "cult of the guru" in educational leadership, this paper draws on an appropriation of Hall's Kardashian index (K-index) for 50 researchers, an analysis of Twitter user networks using NodelXL, and relational theorizing to investigate the ways in which research expertise is being mobilized / recast by educational leadership researchers on Twitter. Establishing an empirical foundation for ongoing dialogue and debate it is argued that the recasting of research expertise to those curating followership, and potentially divorced from research performance, is of timely significance for the ongoing credibility of the field both internally and within the broader academy.
Keywords: 330; Twitter; Kardashian-index; Social media; Cult of the guru; Relational; Auctor; Organizing activity; Spatio-temporal conditions; Followership; Attention